Characterization of the Leptospiral Outer Membrane and Description of Three Novel Leptospiral Membrane Proteins - Haake, David A. (American Society for Microbiology, 2002)
The outer membrane (OM) of the mammalian pathogen Leptospira kirschneri was isolated in the form of membrane vesicles by alkaline plasmolysis and separated from the protoplasmic cylinder by sucrose density gradient ultracentrifugation. All four components of the alkaline plasmolysis buffer, including 1.0 M NaCl, 27% sucrose (wt/vol), 2 mM EDTA, and 10 mM Tris (pH 9), were required for efficient OM release, as judged by recovery of leptospiral lipopolysaccharide. Two populations of OM vesicles (OMVs) were recovered, with peak concentrations found in the sucrose gradient at densities of 1.16 and 1.18 g/ml. Transmission electron microscopy revealed that the more buoyant OMV population was smaller (<0.1 μm in diameter) than the denser OMV population (0.2 to 0.3 μm in diameter). The densities of both populations of OMVs were distinct from that of the protoplasmic-cylinder material, which was found in the sucrose gradient at a density of 1.20 g/ml. The OMV fractions were free of protoplasmic-cylinder material, as judged by immunoblotting with antibodies to the endoflagellar sheath protein, heat shock protein GroEL, and two novel cytoplasmic membrane proteins, lipoprotein LipL31 and transmembrane protein ImpL63. The protein components of the OMVs were characterized by one- and two-dimensional immunoblotting and found to include previously described OM proteins (OMPs), including the porin OmpL1; the lipoproteins LipL32, LipL36, and LipL41; and the peripheral membrane protein P31(LipL45). A number of less well-characterized OMPs were also identified, including those with molecular masses of 16, 21, 21.5, 22, 31, 36, 44, 48, 90, and 116 kDa. The 48-kDa OMP was identified as a novel OM lipoprotein designated LipL48. The use of membrane-specific markers in OM isolation techniques facilitates an accurate description of the leptospiral OM and its components.